The Criteria and Ethical Guidelines for Tax Officer in Islam: a Review of Some Traditional Literature - Rahmad Hakim (Universitas Darussalam Gontor, 2019)
AbstractTax occupies an important role as a source income of the state. With this role, there are several important regulations in taxation, including the obligation for citizens to pay taxes. To enhance the benefit of tax, the criteria and ethical guidelines are needed for tax officers in carrying out their duties, so that the tax collection mechanism runs fairly, more transparent and accountable. This paper aims to analyze the criteria and ethical guidelines for tax officers in Islamic civilization as recorded in some traditional literature. This is qualitative research using the method of documentation in the collection of data. This study concluded that the criteria of tax officer are: first, the free person (not slave). Second, amânah. Third, capable or expert (kafâ'ah). Fourth, meet the criteria of faqîh and mujtahîd (if serves as a determinant of the tax rate (kharâj)). On the other hand, the ethical guidelines for tax officer are: first, no excess conduct for the taxpayers. Second, no persecution. Third, avoid manipulating the value of gold. Fourth, no prize in the form of precious stones. Fifth, collect taxes properly and correctly (in accordance with sharia provisions). Sixth, no tax (kharâj) on people who convert to Muslim. Keywords: Ethics, Taxation, Islamic Taxation, Tax Officer, Islamic Civilization. AbstrakPajak menempati peran penting sebagai sumber pendapatan dari negara. Dengan peran ini ada beberapa peraturan penting dalam perpajakan, termasuk kewajiban bagi warga negara untuk membayar pajak. Untuk meningkatkan manfaat pajak, kriteria dan pedoman etika diperlukan bagi petugas pajak dalam menjalankan tugasnya, sehingga mekanisme pengumpulan pajak berjalan dengan adil, lebih transparan, dan akuntabel. Makalah ini bertujuan untuk menganalisis kriteria dan pedoman etika bagi petugas pajak dalam peradaban Islam sebagaimana dicatat dalam beberapa literatur tradisional. Ini adalah penelitian kualitatif dengan menggunakan metode dokumentasi dalam pengumpulan data. Penelitian ini menyimpulkan bahwa kriteria untuk petugas pajak adalah: pertama, orang bebas (bukan budak). Kedua, amanah. Ketiga, cakap atau ahli (kafâ’ah). Keempat, memenuhi kriteria faqih dan mujtahid (jika berfungsi sebagai penentu tarif pajak (kharâj)). Di sisi lain, pedoman etika untuk petugas pajak adalah: pertama tidak ada perilaku berlebihan untuk wajib pajak. Kedua, tidak ada penganiayaan. Ketiga, hindari memanipulasi nilai emas. Keempat, tidak ada hadiah dalam bentuk batu mulia. Kelima, memungut pajak dengan benar (sesuai dengan ketentuan syariah). Keenam, tidak ada pajak (kharâj) pada orang-orang yang menyamar menjadi Muslim. Kata Kunci: Etika, Perpajakan, Perpajakan Islam, Petugas Pajak, Peradaban Islam.